Autophagy: PolyQ toxic fragment turnover - Duncan, Carlotta (2010)
Recent studies have highlighted the importance of the lysosome in degrading proteins that misfold in neurodegenerative diseases. In this study we explore the role for autophagy in the clearance of an N-terminal caspase-7-generated fragment of ataxin-7, a protein with a pathogenic polyglutamine (polyQ) expansion in the neurodegenerative disease spinocerebellar ataxia 7 (SCA7). Using both cellular and transgenic mouse models of SCA7 we show that the stability of wild-type ataxin-7 is modified by macroautophagy, but not by proteasomal, inhibition, whereas both autophagy and proteasomal degradation have little effect on polyQ-expanded ataxin-7. We also create a post-translational modification-deficient ataxin-7 mutant that has increased protein turnover of both wild-type and polyQ-expanded ataxin-7, mediated through the autophagy pathway. Histological analysis reveals that wild-type ataxin-7 colocalizes with markers of chaperone-mediated autophagy (CMA) and macroautophagy, indicating that both of these mechanisms may play a role in the clearance of ataxin-7. Furthermore, there is an increase in LC3, a marker of autophagy initiation, in the cerebellum of SCA7 transgenic mice. Our findings indicate that the ataxin-7 fragment may be cleared via autophagy and that this process is altered in SCA7. Identification of the different types of autophagy involved in ataxin-7 turnover and the influence of post-translational modifications on these processes will be pursued in future studies.